Restriction endonuclease analysis of local Brucella isolates - Maureen, J.; Bejo, Siti Khairani; Muhid, A.; Jamli, M.; Bahaman, Abdul Rani (Universiti Putra Malaysia Press, 2004)
Six Brucella isolates isolated from local sheep and cattle were examined for the cleavage patterns of their genome by HindIII restriction endonuclease. The DNA fragment patterns obtained from each isolates were compared with reference strains of Brucella melitensis 16M and Brucella abortus strain 99. Eight fragments bands were resolved above 10, 000 base pairs DNA molecular weight markers. It was observed that the DNA fragment patterns of all isolates were similar.